2017
DOI: 10.1002/pam.21972
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Health Insurance on Preventive Care and Health Behaviors: Evidence from the First Two Years of the ACA Medicaid Expansions

Abstract: The U.S. population receives suboptimal levels of preventive care and has a high prevalence of risky health behaviors. One goal of the Affordable Care Act (ACA) was to increase preventive care and improve health behaviors by expanding access to health insurance. This paper estimates how the ACA-facilitated state-level expansions of Medicaid in 2014 affected these outcomes. Using data from the Behavioral Risk Factor Surveillance System, and a difference-in-differences model that compares states that did and did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
466
8
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 418 publications
(503 citation statements)
references
References 58 publications
26
466
8
3
Order By: Relevance
“…11 Broadly speaking, our finding that the Medicaid expansion increased access along some but not all dimensions is consistent with the results from the DD studies by Sommers et al (2015) and Simon et al (2017).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…11 Broadly speaking, our finding that the Medicaid expansion increased access along some but not all dimensions is consistent with the results from the DD studies by Sommers et al (2015) and Simon et al (2017).…”
Section: Resultssupporting
confidence: 79%
“…Our small and insignificant estimates contrast the large, early improvements in these same self-assessed health outcomes seen after the Massachusetts health care reform (Courtemanche and Zapata, 2014;Van der Wees et al, 2013) and randomized Oregon Medicaid experiment (Finkelstein et al, 2012). However, our null results for the Medicaid expansion are consistent with the lack of clear improvements in self-assessed health found by the DD studies in the ACA Medicaid expansion literature Abramowitz, 2016;Simon et al, 2017).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…In the United States alone, these interventions include Medicaid (Currie and Gruber, 1996a;Dafny and Gruber, 2005;Baicker et al, 2013;Finkelstein et al, 2012;Taubman et al, 2014;Tello-Trillo, 2016), Medicare (Lichtenberg, 2002;Card et al, 2008), the Massachusetts universal coverage initiative (Miller, 2012a;Kolstad and Kowalski, 2012;Van der Wees et al, 2013), the 2010 expansion of coverage to young adults under the ACA (Sommers et al, 2013;Antwi et al, 2015;Barbaresco et al, 2015) and the various ACA provisions that took effect in 2014 Courtemanche et al, 2017b;Simon et al, 2017;Miller and Wherry 2017). …”
Section: Introductionmentioning
confidence: 99%
“…The private insurance portion of the ACA seems to have improved access to care, but the evidence with regard to its effect on self-assessed health is decidedly mixed Courtemanche et al, 2017b). Several studies have found that the Medicaid expansion under the ACA led to modest access gains for patients, but had no discernable effect on self-assessed health Courtemanche et al, 2017b;Simon et al, 2017).…”
Section: Introductionmentioning
confidence: 99%